If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2x(x + 6) = 39 Reorder the terms: 7x + 2x(6 + x) = 39 7x + (6 * 2x + x * 2x) = 39 7x + (12x + 2x2) = 39 Combine like terms: 7x + 12x = 19x 19x + 2x2 = 39 Solving 19x + 2x2 = 39 Solving for variable 'x'. Reorder the terms: -39 + 19x + 2x2 = 39 + -39 Combine like terms: 39 + -39 = 0 -39 + 19x + 2x2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -19.5 + 9.5x + x2 = 0 Move the constant term to the right: Add '19.5' to each side of the equation. -19.5 + 9.5x + 19.5 + x2 = 0 + 19.5 Reorder the terms: -19.5 + 19.5 + 9.5x + x2 = 0 + 19.5 Combine like terms: -19.5 + 19.5 = 0.0 0.0 + 9.5x + x2 = 0 + 19.5 9.5x + x2 = 0 + 19.5 Combine like terms: 0 + 19.5 = 19.5 9.5x + x2 = 19.5 The x term is 9.5x. Take half its coefficient (4.75). Square it (22.5625) and add it to both sides. Add '22.5625' to each side of the equation. 9.5x + 22.5625 + x2 = 19.5 + 22.5625 Reorder the terms: 22.5625 + 9.5x + x2 = 19.5 + 22.5625 Combine like terms: 19.5 + 22.5625 = 42.0625 22.5625 + 9.5x + x2 = 42.0625 Factor a perfect square on the left side: (x + 4.75)(x + 4.75) = 42.0625 Calculate the square root of the right side: 6.485560886 Break this problem into two subproblems by setting (x + 4.75) equal to 6.485560886 and -6.485560886.Subproblem 1
x + 4.75 = 6.485560886 Simplifying x + 4.75 = 6.485560886 Reorder the terms: 4.75 + x = 6.485560886 Solving 4.75 + x = 6.485560886 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.75' to each side of the equation. 4.75 + -4.75 + x = 6.485560886 + -4.75 Combine like terms: 4.75 + -4.75 = 0.00 0.00 + x = 6.485560886 + -4.75 x = 6.485560886 + -4.75 Combine like terms: 6.485560886 + -4.75 = 1.735560886 x = 1.735560886 Simplifying x = 1.735560886Subproblem 2
x + 4.75 = -6.485560886 Simplifying x + 4.75 = -6.485560886 Reorder the terms: 4.75 + x = -6.485560886 Solving 4.75 + x = -6.485560886 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.75' to each side of the equation. 4.75 + -4.75 + x = -6.485560886 + -4.75 Combine like terms: 4.75 + -4.75 = 0.00 0.00 + x = -6.485560886 + -4.75 x = -6.485560886 + -4.75 Combine like terms: -6.485560886 + -4.75 = -11.235560886 x = -11.235560886 Simplifying x = -11.235560886Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.735560886, -11.235560886}
| x+5.2=-6.5 | | 15(p^2-1)-16p=0 | | -4=-7x | | 0.1+1.4=1.2x-3 | | 10x+18=4x+60 | | 17/2y=-17 | | 8+3(s-6t)= | | x^2y^4z/(x^2y)3*(x^10y^5z^4)^2/y^3z^2 | | 3(8+3/2y)+4y=7 | | 1/2(n+5)+1/3(n+3)=6 | | 5+2(x-3y)= | | -75=5(7n+6) | | 7t+18-4= | | -1x^2+12x-36=0 | | 2x^4-2x^3-11x^2+4x+8=0 | | 4(3x+7)-6(3x-5)=10x+3(2x-8) | | 4.9x^2+8x-30=0 | | .5(2m+6)=.25(8+8m) | | 3x^2-8x=9 | | 4.9x^2+8t-30=0 | | .25(2m-20)=.25(8-8m) | | (3x+7)(5x-1)= | | -35=5-2x+7x | | (2lb-5)-5(4b+4)=-3 | | 10-24d=4-5(2d+9)+3d | | 35-15x=-8x | | 7k+1=2k-1 | | 8w+w+6w= | | 35-15x=8x | | .5(-12m+6)=.25(-20+8m) | | (-8x-7)(-7x-3)= | | N+19=16 |